Dual-layer detector CT of chest, abdomen, and pelvis with a one-third iodine dose: image quality, radiation dose, and optimal monoenergetic settings. Issue 12 (December 2018) - Nagayama, Y.; Nakaura, T.; Oda, S.; Taguchi, N.; Utsunomiya, D.; Funama, Y.; Kidoh, M.; Namimoto, T.; Sakabe, D.; Hatemura, M.; Yamashita, Y.
Abstract : Aim: To compare the image quality and radiation dose of reduced iodine dose dual-layer detector (DL) computed tomography (CT) with those of a conventional 120 kVp protocol for chest–abdomen–pelvis CT (CAP-CT). Materials and methods: Forty patients with renal dysfunction (estimated glomerular filtrating ratio <45 ml/min/1.73 m 2 ) underwent reduced iodine dose CAP-CT (120 kVp, 200 mg iodine/kg) on DLCT. Virtual monochromatic images (VMI) at 40–70 keV (5 keV interval) were reconstructed retrospectively. Forty matched patients who underwent conventional CAP-CT (120 kVp, 600 mg iodine/kg, iterative reconstruction) were included as controls. The size-specific dose estimate (SSDE), image noise, CT attenuation, and contrast-to-noise ratio (CNR) were compared between the protocols. Two radiologists rated image contrast, image noise, streak artefact, and diagnostic confidence on a five-point scale. Results: The SSDE of the DLCT group was approximately 20% lower than that of the 120 kVp group (15.4±1.9 versus 19.4±2.3 mGy, p< 0.01). DLCT-VMI provided almost constant image noise throughout the range of energies (differences of ≤13%), with the noise being equivalent or lower than 120 kVp in the abdomen. CT attenuation and CNR gradually increased as the energy decreased, with values comparable to 120 kVp being attained at around 45–50 keV. Although streak artefact was accentuated at 40–50 keV ( p< 0.01), the highest scores for diagnostic confidence were assigned at 40 and 45 keV, both of which were equivalent to 120 kVp ( p= 1.0). Conclusion: For CAP-CT with a one-third iodine dose, DLCT-VMI at 40–45 keV allows for a 20% reduction in radiation dose, while preserving image quality comparable to that of conventional 120 kVp protocol. Highlights: Organ and vessel contrast of DLCT-VMI steeply increase as the energy decreases. Image noise of DLCT-VMI is almost constant across each energy. For one-third-iodine CAP-DLCT, VMI at 40–45-keV provides diagnostic image quality. CAP-DLCT decreases radiation dose by 20% compared to conventional120-kVp.